2018
DOI: 10.1098/rspb.2017.1762
|View full text |Cite
|
Sign up to set email alerts
|

Island- and lake-like parallel adaptive radiations replicated in rivers

Abstract: Parallel adaptive radiations have arisen following the colonization of islands by lizards and lakes by fishes. In these classic examples, parallel adaptive radiation is a response to the ecological opportunities afforded by the colonization of novel ecosystems and similar adaptive landscapes that favour the evolution of similar suites of ecomorphs, despite independent evolutionary histories. Here, we demonstrate that parallel adaptive radiations of cichlid fishes arose in South American rivers. Speciation-asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
63
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 66 publications
4
63
1
Order By: Relevance
“…1,38,42,43,46,76,77 ), it is extremely rare in river-dwelling fish assemblages. Thus far, only one case of repeated patterns composed of two riverine adaptive radiations has been documented within the South-American cichlids of the genus Crenicichla from the Paraná and Uruguay Rivers 25,27 . The four riverine radiations of Ethiopian Labeobarbus originated from different ancestral populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,38,42,43,46,76,77 ), it is extremely rare in river-dwelling fish assemblages. Thus far, only one case of repeated patterns composed of two riverine adaptive radiations has been documented within the South-American cichlids of the genus Crenicichla from the Paraná and Uruguay Rivers 25,27 . The four riverine radiations of Ethiopian Labeobarbus originated from different ancestral populations.…”
Section: Discussionmentioning
confidence: 99%
“…Although examples of adaptive radiation in riverine fish are not particularly frequent, they have substantially increased during the last decades. Such evolutionary phenomena have been revealed by molecular data in the African mormyrids, mochokid catfishes and cyprinids [16][17][18][19][20] , as well as in the African and South American cichlids [21][22][23][24][25][26][27] . For example, cichlids of the genus Crenicichla Heckel 1840 from Paraná and Uruguay Rivers demonstrate bright morpho-ecological diversification and trophic resource partitioning.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Evolutionary radiations are well documented from true islands (Gillespie 2009b), but also from ILS. Examples include earthworm mice in mountain tops (Heaney et al 2016), plants on inselbergs (Porembski 2009), cichlid fish in rivers (Burress et al 2018), whitefish species in freshwater lakes (Østbye et al 2006), jellyfish in marine lakes (Dawson and Hamner 2005), cyanobacteria in hot springs (Ward et al 1998, Papke et al 2003, and planthoppers in caves (Wessel et al 2013). However, studies have found that speciation, for example in lakes, occurs in smaller areas than on true islands, and the threshold area for a sharp rise in speciation prevalence in lakes is only a third of that of true islands (Arnott 2009).…”
Section: Evolutionary Radiation Occurrencesmentioning
confidence: 99%
“…While some classic adaptive radiations, such as Australian marsupials, exhibit early bursts in lineage and morphological diversification (Garcia-Navas et al 2018), some equally famous adaptive radiations, such as Darwin's finches, do not (Burns et al 2017). Cichlid fishes, another pillar in the adaptive radiation literature, exhibit dramatic shifts in lineage diversification rates following the colonization of novel ecosystems (Seehausen 2006); however, many of these lineages, including the mega-diverse assemblages in Lakes Malawi and Victoria, may be in the expansion phase and have yet to enter the latter stages of adaptive radiation in which their diversification slows (Burress and Tan 2017;Burress et al 2018). Of the older lineages, including the radiation within Lake Tanganyika, there is also little evidence of early bursts (Harmon et al 2010).…”
Section: Radiationmentioning
confidence: 99%